The Left after the Elections - SUMANTA BANERJEE (Economic and Political Weekly June 2, 2001, 2001)
Now that the dust of the elections has settled, several questions need to be addressed by the Left, if it is to seriously think of chalking out its future. After its debacle in Kerala, will the Left now remain content with its electoral power confined to Tripura and West Bengal? In the rest of India, will it reconcile itself to the role of a minor ally of various regional and centrist parties? Shall we see more of spectacles like the CPI and the CPI(M) tying themselves to the apron strings of the likes of Laloo Yadav and Jayalalitha? Will they be seen on the same platform as the Shiv Sena and the RSS-led Bharatiya Mazdoor Sangh in anti-WTO agitations, as witnessed recently in Maharashtra?